Lesser Grain Borer, Rhyzopertha dominica (Coleoptera, Bostrichidae) - P.G. Koehler (EDIS)
This document provides an overview of the lesser grain borer, Rhyzopertha dominica, a serious pest of stored grains and cereal products. It describes the beetle’s appearance, habits, and biology, including its ability to infest a wide range of products. The article emphasizes the importance of inspection and sanitation in preventing infestations and outlines control measures, including the use of pheromone traps, insect-proof containers, and various pesticides. It also highlights the need for fumigation in cases of large infestations and provides a table of available pesticides for effective management. Publication date: March 1994.